Effect of Mulching on the Growth of Erythrina orientalis (L.) Merill and Polyalthia longifolia var pendula Hook. F. seedlings - Millaa-Armilla, Asli (Universiti Malaysia Sarawak, (UNIMAS), 2005)
Erythrina orientalis and Polyalthia longifolia varpendula seedlings were subjected to 2, 4 and 6 inches of mulching for five months. Mulching is considered as the best alternative for enhancing plant growth and to rehabilitate degraded urban soil. The data on collar diameter, height, number of leaves, soil pH and soil moisture content was analysed using one-way analyses of variance. The results showed that E. orientalis and P. longifolia seedlings showed better diameter, height and number of leaves when treated with 6 inches of mulching. There was a change in the soil pH and moisture content of the experimental soil after 5 months of treatments. Mulching is found to be beneficial in enhancing plant growth, as it will eliminate competition from other vegetation for growing resources such as growing space, light, water and nutrients. The high growth performance of E. orientalis and P. longifolia seedlingsunder 6 inches of mulching can contribute to their survival in the harsh urban landscape